2001
DOI: 10.1073/pnas.191502998
|View full text |Cite
|
Sign up to set email alerts
|

Classification of human lung carcinomas by mRNA expression profiling reveals distinct adenocarcinoma subclasses

Abstract: We have generated a molecular taxonomy of lung carcinoma, the leading cause of cancer death in the United States and worldwide. Using oligonucleotide microarrays, we analyzed mRNA expression levels corresponding to 12,600 transcript sequences in 186 lung tumor samples, including 139 adenocarcinomas resected from the lung. Hierarchical and probabilistic clustering of expression data defined distinct subclasses of lung adenocarcinoma. Among these were tumors with high relative expression of neuroendocrine genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

77
1,543
3
13

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,260 publications
(1,648 citation statements)
references
References 34 publications
77
1,543
3
13
Order By: Relevance
“…Focal adhesion kinase shRNA expression in both human MCF-7 and MDA-MB-231 breast carcinoma cells also resulted in the inhibition of uPA expression. In analysing published gene array data that compared the mRNA profile of benign breast tissue versus breast carcinoma (Sorlie et al, 2001) and normal lung tissue versus lung adenocarcinoma (Bhattacharjee et al, 2001), both FAK and uPA expressions are significantly upregulated in the carcinoma samples. As FAK expression is elevated in a variety of tumor cells and malignant tissues (Gabarra-Niecko et al, 2003), and FAK re-expression in v-Src-transformed FAKÀ/À fibroblasts promotes uPA expression (S Mitra, unpublished results), our findings support the conclusion that enhanced FAK signaling promotes uPA expression in a variety of cell types and that this signaling linkage contributes to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinase shRNA expression in both human MCF-7 and MDA-MB-231 breast carcinoma cells also resulted in the inhibition of uPA expression. In analysing published gene array data that compared the mRNA profile of benign breast tissue versus breast carcinoma (Sorlie et al, 2001) and normal lung tissue versus lung adenocarcinoma (Bhattacharjee et al, 2001), both FAK and uPA expressions are significantly upregulated in the carcinoma samples. As FAK expression is elevated in a variety of tumor cells and malignant tissues (Gabarra-Niecko et al, 2003), and FAK re-expression in v-Src-transformed FAKÀ/À fibroblasts promotes uPA expression (S Mitra, unpublished results), our findings support the conclusion that enhanced FAK signaling promotes uPA expression in a variety of cell types and that this signaling linkage contributes to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Lung adenocarcinomas can form centrally but they tend to be associated with the epithelia of the peripheral airways. Recently, it has been suggested that adenocarcinoma can be classified into two distinct subtypes on the basis of gene expression patterns (Bhattacharjee et al, 2001;Garber et al, 2001). These two subtypes may be delineated by TTF (thyroid transcription factor)-1 expression, which is a lineage marker for peripheral airway cells, including type I and II pneumocytes (Yatabe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To extend these findings to human lung cancer, we performed blinded histological analyses on a wellannotated lung adenocarcinoma set (Bhattacharjee et al, 2001) to assess if any association was present between tumor-associated inflammation and K-ras mutational status. To this end, 76 human lung adenocarcinoma frozen tissue samples stained with hematoxylin and eosin (H&E) were analysed by a pathologist (RP) who was not informed of the K-ras mutational status of the specimens.…”
Section: Human Lung Tumors With Activating K-ras Mutation Have Highermentioning
confidence: 99%